2022
DOI: 10.1007/s00018-022-04244-y
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional regulation of desmosome hyperadhesion by keratin isotypes and desmosomal components

Abstract: Desmosomes are intercellular junctions which mediate cohesion and communication in tissues exposed to mechanical strain by tethering the intermediate filament cytoskeleton to the plasma membrane. While mature desmosomes are characterized by a hyperadhesive, Ca2+-independent state, they transiently loose this state during wound healing, pathogenesis and tissue regeneration. The mechanisms controlling the hyperadhesive state remain incompletely understood. Here, we show that upon Ca2+-induced keratinocyte differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The latter occurs despite attenuated PKCα activity in KRT17 null cells (see Fig. 5 ), suggesting that desmosomes are impacted by PKCα-independent mechanisms in the absence of K17 (47).…”
Section: Resultsmentioning
confidence: 96%
“…The latter occurs despite attenuated PKCα activity in KRT17 null cells (see Fig. 5 ), suggesting that desmosomes are impacted by PKCα-independent mechanisms in the absence of K17 (47).…”
Section: Resultsmentioning
confidence: 96%
“…It has been shown that a decrease in keratin 17 expressions in Ca 2+ ‐induced keratinocyte differentiation prevents the formation of stable and hyper‐adhesive desmosomes. These results highlight the importance of keratin for the formation of these desmosomes, as desmoplakin overexpression fails to form stable desmosomes in the absence of keratin (Büchau et al, 2022). In line with the interaction between keratin and desmosome, the desmosome can arrange suitable sites for the keratin cytoskeleton.…”
Section: Discussionmentioning
confidence: 81%
“…Slug is known to be expressed in the undifferentiated basal cell compartment of the epidermis and is important in the context of epidermal wound healing ( Arnoux et al, 2008 ). Injury is also known to induce the expression of desmosome-associated stress-associated keratins like K6/16/17 that can alter desmoglein expression and function ( Büchau et al, 2022 ). While transcripts encoding these keratins were unchanged in keratinocytes treated with melanoma-conditioned media, in the future, it will be worth more broadly considering how the desmosome-intermediate filament network controls the developing melanoma niche.…”
Section: Discussionmentioning
confidence: 99%